2012
DOI: 10.1080/00927872.2010.523642
|View full text |Cite
|
Sign up to set email alerts
|

Upper Bounds for the Stanley Depth

Abstract: Abstract. Let I ⊂ J be monomial ideals of a polynomial algebra S over a field. Then the Stanley depth of J/I is smaller or equal with the Stanley depth of √ J/ √ I. We give also an upper bound for the Stanley depth of the intersection of two primary monomial ideals Q, Q ′ , which is reached if Q, Q ′ are irreducible, ht(Q + Q ′ ) is odd and √ Q, √ Q ′ have no common variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Finally, let us point out several results that also follow from our main result. The following result was originally proven in Ishaq [Ish12]. See also Seyed Fakhari [SF17] for a different proof.…”
Section: Colon Ideals and Associated Primesmentioning
confidence: 86%
“…Finally, let us point out several results that also follow from our main result. The following result was originally proven in Ishaq [Ish12]. See also Seyed Fakhari [SF17] for a different proof.…”
Section: Colon Ideals and Associated Primesmentioning
confidence: 86%
“…Let I ⊂ J ⊂ S be monomial ideals, Herzog et al [10] showed that the invariant Stanley depth of J/I is combinatorial in nature. The strange thing about Stanley depth is that it shares some properties and bounds with homological invariant depth see ( [10,11,19,18]). Until now mathematicians are not too much familiar with Stanley depth as it is hard to compute, for computation and some known results we refer the readers to ( [1,12,13,14,18]).…”
Section: Introductionmentioning
confidence: 99%
“…Define sdepth P = min i deg v i and the so called Stanley depth of I/J given by sdepth S I/J = max P sdepth P, where P runs in the set of all partitions of P I\J (see [4], [16]). The Stanley depth is not easy to handle, see [4], [14], [7], [5] for some of its properties.…”
Section: Introductionmentioning
confidence: 99%